1975
DOI: 10.1172/jci108048
|View full text |Cite
|
Sign up to set email alerts
|

A functional comparison of the cortical collecting tubule and the distal convoluted tubule.

Abstract: AB STRA CT Electrical and permeability features of the distal convoluted tubule (DCT) and the cortical collecting tubule (CCT) were examined using the technique in which isolated segments of rabbit tubules were perfused in vitro. When rabbits were given a regular diet and tubules were perfused and bathed in artificial solutions simulating plasma ultrafiltrate, the potential difference (PD) was + 3.7+1.9 mV in the CCT and -40.4±2.8 mV in the DCT. When rabbits were given a low sodium, high potassium diet plus i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(56 citation statements)
references
References 45 publications
(82 reference statements)
6
50
0
Order By: Relevance
“…In the salt-treated animals, there was a tendency for a higher FDNA% to the papillary base, although this difference was not statistically significant. These observations are in agreement with (12), loop of Henle (13), and distal convoluted tubule (1) have been shown to be relatively mineralocorticoid insensitive. Therefore, in our opinion, the most likely explanation is an enhanced sodium reabsorption by cortical and(or) medullary collecting tubules.…”
Section: Discussionsupporting
confidence: 90%
“…In the salt-treated animals, there was a tendency for a higher FDNA% to the papillary base, although this difference was not statistically significant. These observations are in agreement with (12), loop of Henle (13), and distal convoluted tubule (1) have been shown to be relatively mineralocorticoid insensitive. Therefore, in our opinion, the most likely explanation is an enhanced sodium reabsorption by cortical and(or) medullary collecting tubules.…”
Section: Discussionsupporting
confidence: 90%
“…This meneuver was done to insure a transepithelial potential difference (PD) lumen negative (2). All animals had free access to food and water before guillotine decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…The PD of CCT from normal rabbits is difficuilt to predict and is dependent, at least in part, on the mineralocorticoid activity (2). The administration of DOCA insures a negative PD which is invariably responsive to PGE2 in doses of 0.1 ,M or greater.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies examining the direct effect of in vitro increases in hydrostatic pressure on tubular function in isolated perfused tubules. They demonstrated that an acute in vitro increase in hydrostatic pressure has no effect on proximal convoluted tubule fluid reabsorption (11) but may alter transport in the cortical collecting tubule since the potential difference fell in response to this maneuver (12). The lack of information on intrinsic tubular function following relief of obstruction prompted us to develop a model of unilateral ureteral obstruction (UUO) and bilateral ureteral obstruction (BUO) for 24 h in the New Zealand White rabbit (13 …”
Section: Introductionmentioning
confidence: 99%